EFFECT OF ETHOS OF WORK AND ORGANIZATIONAL COMMITMENT ON EMPLOYEE PERFORMANCE IN KEMENTRIAN RELIGIOUS OFFICE, KOTA TANGERANG SELATAN - E. Nurzaman AM (International Journal of Education, Information Technology, and Others, 2019)
This study aims to determine the effect of work ethic and organizational commitment on employee performance at the Office of the Ministry of Religion, South Tangerang City. The method used is explanatory research with analysis techniques using statistical analysis with regression testing, correlation, determination and hypothesis testing. The results of this study work ethic have a significant effect on employee performance by 42.3%, hypothesis testing obtained t count> t table or (5.934> 2.011). Organizational commitment has a significant effect on employee performance by 47.2%, hypothesis testing is obtained t count> t table or (6,557> 2,011). Work ethic and organizational commitment simultaneously have a significant effect on employee performance with the regression equation Y = 9.176 + 0.354X1 + 0.422X2. The contribution of the effect was 57.0%, the hypothesis test obtained F count> F table or (31.178> 2,800